Subterranean species of Acipes Attems, 1937 (Diplopoda, Julida, Blaniulidae) - Enghoff, Henrik (2018)
Up to now, nine species have been described in the genus Acipes Attems, 1937 (Enghoff 1983, 1986; Enghoff & Mauriès 1999). Six of these are endemic on the island of Madeira and its satellite islands, one is endemic in the Canary Islands, and two are endemic in continental Spain. One of the latter, A.andalusius Enghoff & Mauriès, 1999, is a blind cave-dweller, whereas the eight others are surface dwellers, mostly associated with forests and all having eyes. Research on subterranean biodiversity of karst areas in Portugal did not match the development in neighboring Spain in the last century (Sendra et al. 2011), although it has been increasing remarkably in recent years, due to the combined efforts of several specialists in different taxonomic groups (Reboleira et al. 2011, Reboleira, 2012). Millipedes of caves in mainland Portugal have not been subjects of study for almost seventy years (Machado, 1946; Reboleira et al. 2013), but recent collecting in Portuguese caves has yielded several species of millipedes, including two new species of Acipes found in caves in the Algarve. We here describe and discuss the two new species. We also put on record a second locality for A. andalusius located 250 km from the type locality. One of the new species shows a configuration of the first pair of male legs that tentatively suggests periodomorphosis.